MEMBRANE MATERIAL DEVELOPMENT FOR SELECTIVE Li+/Na+ SEPARATION - Aprilia, Nungky
In this project, selective binding properties of crown ether polymer were investigated. DB15C5 was incorporated in polymer chain together withsebacic acid and PEG diacid. Based on the size-matching concept between the crown ether cavity and the ionic radius of metal ions, DB15C5 has selective binding with sodium ion (Na+). The presence of hydrophobic group was expected to increase the mechanical strength of the crown ether polymer. The hydrophilic group in this polymer was expected to increases the swelling as such the ions can reach the crown ether more easily. In a consequence of that, the binding ability of crown ether polymer with metal ions was increases.